Comparative Analysis of Factors Forming Consumer Protection Law in Indonesia and The Philippines - Christina Shintya Hapsari; Rommy Hardyansah; Dharma Setiawan Negara; Adi Herisasono; Yeni Vitrianingsih (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Consumer protection law reflects the responsibility of the state in ensuring fairness and justice between business actors and consumers. This study analyzes and compares the historical, social, political, economic, and constitutional factors underlying the formation of consumer protection law in Indonesia and the Philippines.. The results indicate Both nations demonstrate that consumer protection laws serve not only as legal instruments but also as reflections of social transformation and state accountability.